THE IMPLEMENTATION OF QAUNIYAH VERSES BASED ON UNIFICATION CURRICULUM IN SMA TRENSAINS - Shalihin, Rahmat Ryadhush; Bahriya, Fitrohtin; Wantini, Wantini (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2019)
The curriculum in Indonesia has been changed eleven times since 1947th. In fact, the changes that are expected to increase education globally and nationality especially in Islamic Education, have not already revolutionary era yet. As one of independently formal Islamic Education, SMA Trensains Muhammadiyah, Sragen made their own curriculum named ?unification curriculum?. It has a lot of programs implemented in each variety schedule, particularly in Islamic Education. Those unique activities combine not only in theoretical things and classical methods, but also directly applicated the qauniyah verses in the Quran through the technology and learning media. The aims of this paper are to describe how the curriculum in Trensains worked and implemented the verses Quran in different ways from the others. This research uses field research with qualitative methods. Then the data analyze with descriptive ways. The results of this study showed that through the implementation of the unification curriculum in Trensains learning process between Islamic education and natural science collaborated increasing of intellectual and spiritual of students. The students more interactive and productive in integrative curriculum with qauniyah verses in Qur?an and science rather than conventional process.